The Influence of Artificial Intelligence (AI) in Reconstructing History on the @ainusantara Instagram Account - Soleha, Mar'atus (Proceedings of International Conference on Islamic Civilization and Humanities, 2023)
The issue of Artificial Intelligence has affected human life and has entered a new era in the world of education, including in historical studies. AI technology has progressed rapidly, various applications have been developed in various fields, including the field of historical reconstruction. By using qualitative research and an ethnographic approach supported by content analysis, data collection was carried out through interviews with @ainusantara account owners and in-depth observations of @ainusantara Instagram content and netizen responses in the comments column. This research will explore the influence of artificial intelligence in reconstructing history and its impact on our understanding of the past. The influence of the use of AI causes the objectivity of historical events to be further away from material data in the field. Besides AI can provide an overview of how history happened in the past, AI can also cause distortions and wrong interpretations of history. The debate on the use of AI in reconstructing history is still ongoing and a lot of research needs to be done to avoid deviations from actual historical facts. Therefore, the wise use of AI to reconstruct history will be carried out by direct research in the field, then conducting source criticism so as to produce interpretations that are close to historical objectivity.